The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1091/mbc.e13-05-0266
|View full text |Cite
|
Sign up to set email alerts
|

WD60/FAP163 is a dynein intermediate chain required for retrograde intraflagellar transport in cilia

Abstract: WD60/FAP163 is identified as an additional intermediate chain of the dynein that powers retrograde intraflagellar transport. Lack of WD60/FAP163 results in a severe ciliary assembly defect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 44 publications
2
47
1
1
Order By: Relevance
“…Clear homologues of DIC5/FAP133 and of the other intermediate dynein chain, WD60/FAP163, could not be identified in C. elegans (Rompolas et al. , 2007; Patel-King et al. , 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Clear homologues of DIC5/FAP133 and of the other intermediate dynein chain, WD60/FAP163, could not be identified in C. elegans (Rompolas et al. , 2007; Patel-King et al. , 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The sequence of a second dynein intermediate chain (D1bIC1/FAP163, encoded by DIC6 ) is closely related to that of D1bIC2 (Patel-King et al, 2013). Biochemical analysis showed that it is in the same complex as D1bIC2 and LC8 and is transported by IFT in Chlamydomonas .…”
Section: Composition Of the Mainstream Ift Dynein – Cytoplasmic Dyneimentioning
confidence: 99%
“…In addition, the discovery of novel disease‐associated genes can shed further light on biological processes disrupted in disease states. For example, two of the genes identified by analysis of the current cohort, WDR60 and WDR34 , are homologous to genes in lower organisms that have been implicated as components of cytoplasmic dynein motors . As the vertebrate cytoplasmic dynein‐2 motor responsible for retrograde IFT is not well‐defined at this stage, these data provide valuable insight into the structure of this complex.…”
Section: Discussionmentioning
confidence: 89%